Effect of Engine Speed on Performance adn Emissions of a Dual Chamber Spark Ignition Engine - Chailulillah Rangkuti (Universitas Gadjah Mada, 2000)
Effect of Engine Speed on Performance adn Emissions of a Dual Chamber Spark Ignition Engine